Asymmetric Explanations of Group Differences: Experimental Evidence of Foucault's Disciplinary Power. Issue 3 (5th March 2013) - Hegarty, Peter; Bruckmüller, Susanne
Abstract: Whilst the same group differences can be explained in many ways, explanations of group differences tend to spontaneously figure the distinctive attributes of lower‐status groups against a background norm of high‐status groups' attributes. We suggest that this asymmetry occurs in the explanations of scientists and laypeople who have been influenced by the history of 'disciplinary power' which works to disempower lower‐status people by making them visible to the human sciences. We argue that social groups who are habitually studied first in research programs, more commonly encountered social groups, and prototypical social groups are all less likely than their counterparts to be marked in spontaneous explanations of empirical group differences. We present evidence that groups who are explicitly mentioned in such explanations are assumed to be lower in power. We describe some limitations to current knowledge about such asymmetric explanations and suggest some directions for further research, including our thoughts about how to integrate existing findings with the possibility of formulating cognitive alternatives to the status quo among minority groups.